Melt alkalized attapulgite / platinum-based transition bimetallic catalyst as well as preparation method and application thereof
By using a molten alkalized concave-blocking rock stone/platinum-based transition bimetallic catalyst, the problems of high cost and low efficiency of traditional glycerol hydrogenolysis reaction are solved, and efficient catalyzing glycerol aqueous phase reforming under low reaction conditions is achieved to generate high-efficiency hydrogen and value-added products.
Patent Information
- Application Number
- CN202510071507.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Traditional glycerol hydrogenolysis reactions require high pressure hydrogen atmosphere and high reaction temperatures, resulting in high cost and low selectivity of hydrogen production efficiency and value-added liquid products.
A melt-alkalised concave-rodite/platinum-based transition bimetallic catalyst is used that promotes the glycerol aqueous phase reforming reaction to generate hydrogen and value-added products by utilizing the bimetallic active sites of platinum and transition metals without additional hydrogen sources.
It has achieved efficient catalytic glycerol aqueous phase reforming under low reaction conditions to generate high-efficiency hydrogen and value-added products 1,2-propanediol and 1,3-propanediol. The catalyst has high anti-sintering and anti-carbon deposit capabilities, meeting the requirements of industrial applications.
Smart Images

Figure CN119857497A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a melt-alkalized attapulgite / platinum-based transition bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] Glycerol is a cheap renewable resource, which is generally obtained from renewable raw materials (including vegetable oils, animal fats, cellulose, etc.) by hydrolysis or hydrodeoxygenation. Hydrogen energy, as a new type of renewable energy, has a good development prospect. Aqueous phase reforming (APR) is a promising method for preparing cheap renewable hydrogen from glycerol as a raw material. It has been widely studied because of its low temperature and no need to evaporate glycerol and water.
[0003] In addition, the catalytic conversion of glycerol into high value-added products is also an important issue for sustainable production. The value-added of residual glycerol through catalytic conversion has attracted widespread attention. For example, propanol, propylene glycol or C3 hydrocarbons (propylene, propane) can be obtained from glycerol through a deoxygenation process. The catalytic hydrogenolysis of glycerol to produce 1,2-propylene glycol (1,2-PDO) is a very effective glycerol conversion pathway because 1,2-propylene glycol can be widely used in the production of polyester resins and pharmaceuticals, and 1,3-propylene glycol (1,3-PDO) as a monomer of polytrimethyl terephthalate (PTT) has a high industrial demand. The catalytic production of 1,3-propylene glycol through the selective hydrogenolysis of glycerol is one of the most promising industrial application reactions in the field of biomass catalysis.
[0004] However, traditional hydrogenolysis requires a high-pressure hydrogen atmosphere and a high reaction temperature (generally 260-280°C), which often costs more. How to reduce costs while achieving better hydrogen production efficiency and selectivity for value-added liquid products by designing catalysts has become the current research focus. Summary of the invention
[0005] The main purpose of the present invention is to provide a catalyst having low reaction condition requirements, high conversion efficiency and selectivity, and capable of catalyzing glycerol aqueous phase reforming to produce hydrogen and value-added products without an additional hydrogen source, as well as a preparation method and application thereof.
[0006] To achieve the above-mentioned purpose, the present invention provides a molten alkalized attapulgite / platinum-based transition bimetallic catalyst, comprising a carrier and an active component loaded on the carrier, wherein the carrier is molten alkalized attapulgite, the active component is platinum and a transition metal, and the transition metal is selected from iron, cobalt, nickel and copper.
[0007] Furthermore, the content of platinum is 1-5wt%, and the content of transition metal is 5-10wt%.
[0008] Furthermore, the molten alkalized attapulgite is prepared by the following method: placing the attapulgite in a sodium hydroxide ethanol solution, heating and stirring until the ethanol is completely evaporated, drying the remaining solid, and then heating it to 550-700°C at a heating rate of 1-5°C / min for 5-10 hours, cooling the calcined product, adding deionized water, stirring and dispersing it, and then standing it, taking out the flocculent layer, filtering and washing it with deionized water, and drying the filter cake to obtain the molten alkalized attapulgite.
[0009] Furthermore, the concentration of the sodium hydroxide ethanol solution is 3-5 mol / L, and the ratio of attapulgite to the sodium hydroxide ethanol solution is 40 g:1 L.
[0010] Furthermore, the temperature condition of the heating and stirring treatment is 150 to 220°C.
[0011] Furthermore, the drying process is carried out at a temperature of 105 to 120° C. and a time of 12 to 24 hours.
[0012] Furthermore, the drying process is carried out at a temperature of 105 to 120° C. and a time of 12 to 24 hours.
[0013] The present invention also provides a method for preparing the above-mentioned molten alkalized attapulgite / platinum-based transition bimetallic catalyst, comprising the following steps: dissolving precursor salts of platinum and transition metals in anhydrous ethanol, adding molten alkalized attapulgite, then heating and stirring until all the ethanol is evaporated, drying the remaining solid, grinding it into powder, and finally calcining it in an air atmosphere, and then cooling it to room temperature to obtain the molten alkalized attapulgite / platinum-based transition bimetallic catalyst.
[0014] Furthermore, the temperature condition of the heating and stirring treatment is 80 to 95°C.
[0015] Furthermore, the drying treatment conditions are a temperature of 105 to 120° C. and a time of 12 to 24 hours.
[0016] Furthermore, the specific process of the calcination treatment is: raising the temperature to 400-700° C. at a heating rate of 5-10° C. / min, and then calcining at this temperature for 6-24 hours.
[0017] The present invention also provides the use of the above-mentioned melt-alkalized attapulgite / platinum-based transition bimetallic catalyst in catalyzing glycerol aqueous phase reforming to produce hydrogen and value-added products.
[0018] The present invention also provides the above-mentioned method for catalyzing the aqueous phase reforming of glycerol to produce hydrogen and value-added products, comprising the following steps: putting glycerol, deionized water and the molten alkalized attapulgite / platinum-based transition bimetallic catalyst as described in any one of claims 1 to 4 into a reactor, and conducting a sealed reaction under a nitrogen atmosphere.
[0019] Furthermore, the mass ratio of glycerol, water and catalyst is 9:21:0.1-0.5, and the reaction conditions are temperature 200-240° C. and time 1-4 h.
[0020] Attapulgite is a kind of aluminosilicate with high silicon content. It has a well-developed internal void structure, large surface area and strong adsorption capacity. It can fully disperse the catalytic active components and adsorb the reactant molecules. Using attapulgite as a carrier, the alkalinized attapulgite is synthesized by high-temperature melting under the action of inorganic base. The high structural stability of attapulgite is retained. The original skeleton silicon and aluminum can be effectively destroyed through molten alkali treatment, and the acidity of the carrier is effectively improved, so that the oxidative dehydrogenation and hydrogenation reactions of glycerol and intermediates can be carried out at more acid sites, thereby increasing the yield of 1,2-propylene glycol and 1,3-propylene glycol, and optimizing the specific surface area and pore structure, which is conducive to the high dispersion of loaded metals.
[0021] Precious metal platinum can effectively promote the dehydrogenation reaction in glycerol molecules. In the process of glycerol aqueous phase reforming, the platinum catalyst adsorbs glycerol molecules and activates the CH bond, so that the glycerol molecules can be dehydrogenated to generate hydrogen and other products (such as propylene alcohol, ethylene, propylene, etc.). Transition metal oxides (Ni, Co, Fe, Cu) not only improve the anti-sintering ability of active metals by interacting with active components and carriers, but also the high surface oxygen defect concentration is conducive to promoting the activation of H2O and increasing the number of active oxygen species on the catalyst surface, which is conducive to the water gas shift reaction (WGS), promoting the forward progress of the reaction, and promoting the conversion of carbon-containing intermediates (C=O, C=C, C=CH) into carbon-containing small molecules (CH4, CO2), thereby inhibiting the generation of carbon deposition. Fe2O3 and Co3O4, as multivalent metal oxides, have good redox properties and high oxygen mobility. The present invention prepares a melt-alkalized attapulgite / platinum-based transition bimetallic, which is conducive to promoting the removal of carbon on the catalyst surface, while improving the metal-carrier / metal oxide interlayer interaction and realizing the anchoring of the active precious metal platinum.
[0022] The beneficial effects of the present invention are embodied in:
[0023] 1. The melt-alkalized attapulgite prepared by the present invention is green and economical, and has high structural stability. It has a developed pore structure and a large specific surface area, which allows glycerol molecules with a kinetic diameter of 0.61 nm to enter its pores, significantly improving the adsorption and activation capacity of glycerol molecules.
[0024] 2. The catalyst of the present invention adopts Pt-based and transition element bimetallic active metal sites to ensure that the catalyst has good dehydrogenation performance, accelerates the cracking of glycerol CH, OH and CC bonds, and further promotes the production of H2.
[0025] 3. Compared with single-loaded transition metal catalysts, the catalyst of the present invention can enhance the interaction with active components and carriers by constructing dual sites of Pt and transition metals, and improve the anti-sintering ability of active metals; in addition, the catalyst surface has higher oxygen vacancy defects, which promotes the activation of water, is conducive to the water gas shift reaction (WGS), further increases the hydrogen production, and is conducive to promoting the activation of CO2 and increasing the number of active oxygen species on the catalyst surface, thereby promoting the removal of carbon deposits. Therefore, the catalyst has high resistance to sintering of active components, anti-carbon deposition and high catalytic stability, meeting the requirements for the use of industrial catalysts.
[0026] 4. The catalyst of the present invention can be used for glycerol aqueous phase reforming to produce hydrogen and value-added products without an additional hydrogen source. Its strong acid sites are conducive to the dehydration of glycerol to form hydroxyacetone, and further hydrogenation at the acid sites to produce value-added liquid products such as 1,2-propylene glycol and 1,3-propylene glycol, showing good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The raw material is attapulgite and molten alkalized attapulgite. 29 Si NMR spectroscopy.
[0028] Figure 2 The raw material is attapulgite and molten alkalized attapulgite. 27 A1 NMR spectrum.
[0029] Figure 3 This is the TEM image of the raw material attapulgite.
[0030] Figure 4 This is the TEM image of melt-alkalized attapulgite.
[0031] Figure 5 N2 adsorption-desorption isotherm and pore size distribution diagram of raw material attapulgite.
[0032] Figure 6 The N2 adsorption-desorption isotherm and pore size distribution diagram of melt-alkalized attapulgite.
[0033] Figure 7 These are the XRD patterns of raw material attapulgite, melt-alkalized attapulgite, and various catalysts. DETAILED DESCRIPTION
[0034] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be noted that the following embodiments do not limit the protection scope of the present invention.
[0035] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or can be obtained by existing known methods; unless otherwise specified, the methods used in the examples of the present invention are methods known to those skilled in the art.
[0036] Example 1
[0037] Preparation of Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0038] The theoretical content of the catalyst components prepared in this embodiment is: 1wt% of platinum (Pt), 5wt% of cobalt (Co), and the remainder is melt-alkalized attapulgite; the specific preparation method is as follows:
[0039] (1) 40 g of raw material attapulgite is placed in 1 L, 3 mol / L sodium hydroxide ethanol solution, and stirred at a temperature of 150° C. and a rotation speed of 400 r / min until the ethanol is completely evaporated. The remaining solid is dried at 120° C. for 12 h, and then placed in a muffle furnace and heated to 550° C. at a heating rate of 1° C. / min for 10 h. After the calcined product is cooled to room temperature, 2 L of deionized water is added, stirred and dispersed, and then allowed to stand for 30 min. At this time, a precipitate is deposited at the bottom of the water body, and floccules are suspended in the upper layer of the water body. The floccules layer is taken out, filtered and washed with deionized water until neutral, and the filter cake is dried at 105° C. for 24 h to obtain molten alkalized attapulgite;
[0040] (2) 0.0323 g of platinum acetylacetonate and 0.2641 g of Co(NO3)2·6H2O were added to 100 mL of anhydrous ethanol and stirred thoroughly to dissolve to form a uniform solution. Then, 1.0000 g of molten alkalized attapulgite was added to the above solution and stirred at a temperature of 95°C and a rotation speed of 100 r / min until all the ethanol was evaporated. The remaining solid was dried at 105°C for 24 h and then ground into a solid powder. The solid powder was placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min under an air flow of 100 mL / min. The temperature was then kept constant at 700°C for 6 h and then naturally cooled to room temperature to obtain a molten alkalized attapulgite / platinum-based transition bimetallic catalyst with a platinum content of 1 wt% and a cobalt content of 5 wt%, which was recorded as 1Pt5Co / A-OH.
[0041] Example 2
[0042] Preparation of Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0043] The theoretical content of the catalyst components prepared in this embodiment is: 1wt% of platinum (Pt), 5wt% of nickel (Ni), and the remainder is melt-alkalized attapulgite; the specific preparation method is as follows:
[0044] (1) 40 g of raw material attapulgite is placed in 1 L, 4 mol / L sodium hydroxide ethanol solution, and stirred at a temperature of 170° C. and a rotation speed of 400 r / min until the ethanol is completely evaporated. The remaining solid is dried at 115° C. for 16 h, and then placed in a muffle furnace and heated to 600° C. at a heating rate of 2° C. / min for 8 h. After the calcined product is cooled to room temperature, 2 L of deionized water is added, stirred and dispersed, and then allowed to stand for 30 min. At this time, a precipitate is deposited at the bottom of the water body, and floccules are suspended in the upper layer of the water body. The floccules layer is taken out, filtered and washed with deionized water until neutral, and the filter cake is dried at 110° C. for 20 h to obtain molten alkalized attapulgite;
[0045] (2) 0.0323 g of platinum acetylacetonate and 0.2650 g of Ni(NO3)2·6H2O were added to 100 mL of anhydrous ethanol and stirred thoroughly to dissolve to form a uniform solution. Then, 1.0000 g of molten alkalized attapulgite was added to the above solution and stirred at a temperature of 90°C and a rotation speed of 100 r / min until all the ethanol was evaporated. The remaining solid was dried at 110°C for 20 h and then ground into a solid powder. The solid powder was placed in a tubular furnace and heated to 600°C at a heating rate of 8°C / min under an air flow of 100 mL / min, then calcined at a constant temperature of 600°C for 12 h, and finally naturally cooled to room temperature to obtain a molten alkalized attapulgite / platinum-based transition bimetallic catalyst with a platinum content of 1 wt% and a nickel content of 5 wt%, which was recorded as 1Pt5Ni / A-OH.
[0046] Example 3
[0047] Preparation of Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0048] The theoretical content of the catalyst components prepared in this embodiment is: 1wt% of platinum (Pt), 5wt% of iron (Fe), and the remainder is melt-alkalized attapulgite; the specific preparation method is as follows:
[0049] (1) 40 g of raw material attapulgite is placed in 1 L, 4 mol / L sodium hydroxide ethanol solution, and stirred at a temperature of 200 ° C. and a rotation speed of 400 r / min until the ethanol is completely evaporated. The remaining solid is dried at 110 ° C. for 20 h, and then placed in a muffle furnace and heated to 650 ° C. at a heating rate of 3 ° C. / min for 7 h. After the calcined product is cooled to room temperature, 2 L of deionized water is added, stirred and dispersed, and then allowed to stand for 30 min. At this time, a precipitate is deposited at the bottom of the water body, and floccules are suspended in the upper layer of the water body. The floccules layer is taken out, filtered and washed with deionized water until neutral, and the filter cake is dried at 115 ° C. for 16 h to obtain molten alkalized attapulgite;
[0050] (2) 0.0323 g of platinum acetylacetonate and 0.3868 g of Fe(NO3)2·9H2O were added to 100 mL of anhydrous ethanol and stirred thoroughly to dissolve to form a uniform solution. Then, 1.0000 g of molten alkalized attapulgite was added to the above solution and stirred at a temperature of 80°C and a rotation speed of 100 r / min until all the ethanol was evaporated. The remaining solid was dried at 115°C for 16 h and then ground into a solid powder. The solid powder was placed in a tubular furnace and heated to 500°C at a heating rate of 6°C / min under an air flow of 100 mL / min, then calcined at a constant temperature of 500°C for 18 h, and finally naturally cooled to room temperature to obtain a molten alkalized attapulgite / platinum-based transition bimetallic catalyst with a platinum content of 1 wt% and an iron content of 5 wt%, which was recorded as 1Pt5Fe / A-OH.
[0051] Example 4
[0052] Preparation of Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0053] The theoretical content of the catalyst components prepared in this embodiment is: 1wt% of platinum (Pt), 5wt% of copper (Cu), and the remainder is melt-alkalized attapulgite; the specific preparation method is as follows:
[0054] (1) 40 g of raw material attapulgite is placed in 1 L, 5 mol / L sodium hydroxide ethanol solution, and stirred at a temperature of 220° C. and a rotation speed of 400 r / min until the ethanol is completely evaporated. The remaining solid is dried at 105° C. for 24 h, and then placed in a muffle furnace and heated to 700° C. at a heating rate of 5° C. / min for 5 h. After the calcined product is cooled to room temperature, 2 L of deionized water is added, stirred and dispersed, and then allowed to stand for 30 min. At this time, a precipitate is deposited at the bottom of the water body, and floccules are suspended in the upper layer of the water body. The floccules layer is taken out, filtered and washed with deionized water until neutral, and the filter cake is dried at 120° C. for 12 h to obtain molten alkalized attapulgite;
[0055] (2) 0.0323 g of platinum acetylacetonate and 0.2033 g of Cu(NO3)2·3H2O were added to 100 mL of anhydrous ethanol and stirred thoroughly to dissolve to form a uniform solution. Then, 1.0000 g of molten alkalized attapulgite was added to the above solution and stirred at a temperature of 85°C and a rotation speed of 100 r / min until all the ethanol was evaporated. The remaining solid was dried at 120°C for 12 h and then ground into a solid powder. The solid powder was placed in a tubular furnace and heated to 400°C at a heating rate of 5°C / min under an air flow of 100 mL / min, then calcined at a constant temperature of 400°C for 24 h, and finally naturally cooled to room temperature to obtain a molten alkalized attapulgite / platinum-based transition bimetallic catalyst with a platinum content of 1 wt% and a copper content of 5 wt%, which was recorded as 1Pt5Cu / A-OH.
[0056] Example 5
[0057] Preparation of Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0058] In this example, the catalyst was prepared in the same manner as in Example 3, with the only difference being that the amount of Fe(NO3)2·9H2O was adjusted to 0.7349 g, and a molten alkalized attapulgite / platinum-based transition bimetallic catalyst having a Pt content of 1 wt% and an iron content of 10 wt% was finally obtained, which was recorded as 1Pt10Fe / A-OH.
[0059] Example 6
[0060] Preparation of Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0061] In this example, the catalyst was prepared in the same manner as in Example 3, except that the amount of platinum acetylacetonate was adjusted to 0.1615 g, and a molten alkalized attapulgite / platinum-based transition bimetallic catalyst having a Pt content of 5 wt% and an iron content of 5 wt% was finally obtained, which was recorded as 5Pt5Fe / A-OH.
[0062] Comparative Example 1
[0063] In this comparative example, the catalyst was prepared in the same manner as in Example 3, except that the molten alkalized attapulgite was replaced with raw attapulgite to obtain a attapulgite / platinum-based transition bimetallic catalyst having a platinum content of 1 wt% and an iron content of 5 wt%, recorded as 1Pt5Fe / A-Raw.
[0064] Comparative Example 2
[0065] In this comparative example, the catalyst was prepared in the same manner as in Example 3, except that the addition of platinum acetylacetonate was omitted and the amount of Fe(NO3)2·9H2O was adjusted to 0.3868 g, thereby obtaining a molten alkalized attapulgite / iron metal catalyst having an Fe content of 5 wt%, which was recorded as 5Fe / A-OH.
[0066] Comparative Example 3
[0067] In this comparative example, the catalyst was prepared in the same manner as in Example 3, except that the addition of Fe(NO3)2·9H2O was omitted and the amount of platinum acetylacetonate was adjusted to 0.0323 g, thereby obtaining a molten alkalized attapulgite / platinum metal catalyst having a Pt content of 1 wt%, recorded as 1Pt / A-OH.
[0068] Experimental Example 1
[0069] Structure Determination of Attapulgite and Melt-Alkalinized Attapulgite / Pt-Based Transition Bimetallic Catalysts
[0070] The structural analysis of the raw material attapulgite (denoted as A-Raw), the molten alkalized attapulgite obtained in Example 3 (denoted as A-OH), and the catalysts obtained in Examples 1 to 5 was performed. The results are as follows: Figures 1 to 7 shown.
[0071] See also Figure 1 The raw material attapulgite has detection peaks of tetrahedral silicon at -92 and -97 ppm. After being treated with molten alkali, the alkalized attapulgite shows a large peak at -85 ppm belonging to tetrahedral silicon four-substituted aluminum, indicating that the molten alkali treatment completely destroys the unique silicon skeleton of the original attapulgite.
[0072] See also Figure 2 Only one detection peak belonging to hexacoordinated aluminum was detected at 8ppm in the raw material attapulgite. After being treated with molten alkali, the intensity of the detection peak of the alkalized attapulgite at 8ppm increased eightfold, and a detection peak belonging to tetracoordinated aluminum was detected at 65ppm, indicating that the molten alkali treatment destroyed the original aluminum skeleton and formed a carrier rich in tetracoordinated aluminum and hexacoordinated aluminum with high acid sites, which can effectively improve the oxidative decomposition performance of glycerol.
[0073] See also Figure 3 , Figure 4 ,from Figure 3 The TEM image shows that the raw material attapulgite is a rod-shaped silicon-based material. After being treated with molten alkali, Figure 4 It can be seen from the TEM image that the molten alkalized attapulgite is an amorphous silicon-based carrier, indicating that the structural skeleton of the rod-shaped substrate of attapulgite is crushed under the condition of high-temperature molten alkali, forming an amorphous silicon-based carrier with a high specific surface area.
[0074] See also Figure 5 , Figure 6 Through the isotherms and pore size distribution diagrams of attapulgite before and after melt alkali treatment, it can be seen that the melt alkali-treated attapulgite has a type III isotherm, accompanied by an H4-type hysteresis loop, which is an obvious mesoporous structure, with a higher specific surface area and a larger pore size, forming more defect sites that are beneficial to the loading of active metals. The larger specific surface area and larger pore size are more conducive to glycerol adsorption.
[0075] See also Figure 7 , XRD spectra of various metals loaded Figure 2 The characteristic diffraction peaks of Pt were detected at θ=39.8° and 46.4°, indicating the successful loading of Pt. The catalyst used in the optimal group Example 3 had lower characteristic peaks of Pt and Fe, indicating that Pt, Fe and the carrier have stronger interactions, promoting high dispersion of metals.
[0076] Experimental Example 2
[0077] Catalytic Performance Test of Attapulgite and Melt-alkalized Attapulgite / Pt-based Transition Bimetallic Catalysts
[0078] Test method: Weigh 9g glycerol, 21g deionized water (the concentration of this glycerol aqueous solution system is 30wt%) and 0.1-0.5g catalyst into a high-pressure reactor, fill with 1.0-4.0MPa high-purity nitrogen, and then seal and react for 1-4h at a temperature of 200-240°C and a stirring rate of 450-550r / min. After the reaction is completed, quickly cool to room temperature with ice water, collect the gas product with an air bag and transfer it to a chromatograph to measure the gas product composition, open the reactor, and use a sand core funnel to separate the liquid and solid products; then, the liquid product is stored in a brown reagent bottle and its liquid product composition is determined by a gas chromatograph.
[0079] The specific reaction conditions and results are shown in Table 1.
[0080] Table 1
[0081]
[0082] Note: Catalyst life refers to the usage time when the glycerol conversion rate of the catalyst decreases by 50%.
[0083] From the above results, it can be concluded that the present invention can achieve a high rate of hydrogen production under a nitrogen atmosphere, and in the absence of an additional hydrogen source, the catalyst can realize the self-transfer hydrogenolysis of glycerol molecules in a glycerol water solvent system to generate value-added products 1,2-propylene glycol and 1,3-propylene glycol, achieving a glycerol conversion rate of more than 80%, wherein the yield of 1,2-propylene glycol exceeds 25%, the yield of 1,3-propylene glycol exceeds 23%, and the hydrogen production rate is above 300 μmol / g / min. Among them, the optimal group embodiment 3 can achieve a hydrogen production rate of 795 μmol / g / min, and the liquid products 1,2-propylene glycol and 1,3-propylene glycol generated by the self-transfer hydrogenolysis of glycerol molecules to generate value-added products have 46% and 37% selectivity, respectively, and the conversion rate of glycerol is as high as 92%. In comparison of the two pure carriers, the molten alkalized attapulgite has higher catalytic performance, indicating that the molten alkali treatment can effectively destroy the original skeleton silicon and aluminum, effectively improve the acidity of the carrier, thereby carrying out oxidative dehydrogenation and hydrogenation reactions of glycerol and intermediates at more acid sites, improving the yield of 1,2-propylene glycol and 1,3-propylene glycol, and optimizing the specific surface area and pore structure, which is conducive to the high dispersion of the loaded metal. In contrast to the effects of different platinum and iron loadings on catalysis, the appropriate content of platinum and iron in Example 3 has a higher hydrogen production rate and a higher proportion of selectivity of value-added liquid products.
[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A melt-alkalized attapulgite / platinum-based transition bimetallic catalyst, characterized in that: The invention comprises a carrier and an active component loaded on the carrier. The carrier is molten alkalized attapulgite. The active component is platinum and a transition metal. The transition metal is selected from iron, cobalt, nickel and copper.
2. The melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to claim 1, characterized in that: The content of platinum is 1-5wt%, and the content of transition metal is 5-10wt%.
3. The melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to claim 1 or 2, characterized in that: The molten alkalized attapulgite is prepared by the following method: placing the attapulgite in a sodium hydroxide ethanol solution, heating and stirring until the ethanol is completely evaporated, drying the remaining solid, and then heating the temperature to 550-700°C at a heating rate of 1-5°C / min for 5-10 hours, cooling the calcined product, adding deionized water, stirring and dispersing, and then standing for a treatment, taking out the flocculent layer, filtering and washing with deionized water, and drying the filter cake to obtain the molten alkalized attapulgite.
4. The melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to claim 3, characterized in that: The temperature condition for the heating and stirring treatment is 150 to 220°C.
5. The method for preparing the melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: dissolving precursor salts of platinum and transition metals in anhydrous ethanol, adding molten alkalized attapulgite, then heating and stirring until all the ethanol evaporates, drying the remaining solid, grinding it into powder, and finally calcining it in an air atmosphere, and then cooling it to room temperature to obtain the molten alkalized attapulgite / platinum-based transition bimetallic catalyst.
6. The method for preparing the melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to claim 5, characterized in that: The temperature condition for the heating and stirring treatment is 80 to 95°C.
7. The method for preparing the melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to claim 5, characterized in that: The specific process of the calcination treatment is: heating the temperature to 400-700°C at a heating rate of 5-10°C / min, and then calcining at this temperature for 6-24 hours.
8. Use of the melt-alkalized attapulgite / platinum-based transition bimetallic catalyst according to any one of claims 1 to 4 in catalyzing the aqueous phase reforming of glycerol to produce hydrogen and value-added products.
9. A method for producing hydrogen and value-added products by catalytic aqueous phase reforming of glycerol, characterized in that: The following steps are involved: Glycerol, deionized water and the molten alkalized attapulgite / platinum-based transition bimetallic catalyst according to any one of claims 1 to 4 are placed in a reactor and a sealed reaction is carried out under a nitrogen atmosphere.
10. The method for producing hydrogen and value-added products by catalytic aqueous phase reforming of glycerol as claimed in claim 9, characterized in that: The mass ratio of glycerol, water and catalyst is 1:9-21:0.1-0.5, and the reaction conditions are temperature 200-240°C and time 1-4h.
Citation Information
Patent Citations
Continuous process for the manufacture of ethylene glycol
CA1170644A
Platinum-cobalt / attapulgite catalyst and preparation method and application thereof
CN107376936A
Methanation catalyst and preparation method thereof
CN110639543A
Denitrification catalyst as well as preparation method and denitrification method thereof
CN110773168A
Method for synthesizing Al-MCM-41 mesoporous material by utilizing attapulgite and application of Al-MCM-41 mesoporous material
CN111821943A